1968
DOI: 10.1111/j.1360-0443.1968.tb05272.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspective*

Abstract: Opium, cannabis and cocaine have a long and colourful history which can be seen in perspective at the beginning of this century. The questions asked then were very like those we are asking now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our longitudinal study on clinical and histomorphological features in 114 patients with AMM confirmed the remarkable variability of hematological as well as histological findings in this disorder and further demonstrated that these certainly reflect different stages in the extent of disease (Lewis, 1985;Georgii et al, 1984a,b;Burkhardt er al., 1984Burkhardt er al., , 1986Geary, 1985). Consequently all these features were thought to represent static parameters obtained at variable periods in the progress of AMM.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Our longitudinal study on clinical and histomorphological features in 114 patients with AMM confirmed the remarkable variability of hematological as well as histological findings in this disorder and further demonstrated that these certainly reflect different stages in the extent of disease (Lewis, 1985;Georgii et al, 1984a,b;Burkhardt er al., 1984Burkhardt er al., , 1986Geary, 1985). Consequently all these features were thought to represent static parameters obtained at variable periods in the progress of AMM.…”
Section: Discussionsupporting
confidence: 75%
“…Histological studies of the bone marrow suggested that AMM may include (pan-)hyperplastic as well as osteosclerotic changes (Pitcock et al, 1962;Silverstein, 1975;Buyssens and Bourgeois, 1977;Georgii et al, 1984a,b;Lewis, 1985). These were thought to reflect also different phases in the progress ofdisease (Burkhardt et al, ,1986Georgii et al, 1984a,b;Frisch et al, 1984;Lewis, 1985;Frisch and Bartl, 1985).…”
Section: Histological Studiesmentioning
confidence: 91%
See 3 more Smart Citations